2017
DOI: 10.1007/978-3-319-52593-8_13
|View full text |Cite
|
Sign up to set email alerts
|

The Goals Approach: Agile Enterprise Driven Software Development

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. Abstract. Continuous Business Process Improvement (BPI) is necessary in order to maintain and develop the enterprise competitiveness. However, achieving a level of software development performance that matches enterprise needs in terms of producing noticeable results within small amounts of time is a persnickety task, mainly because most available methods do not deliver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…As a paper can mention more than one EA category element, the total count of elements in Figure 3 is greater than the number of selected publications. Figure 3 reveals that the most common were framework (28), followed by AD papers (21), and views/viewpoints (20). It is noteworthy that Archimate is mentioned in a total of 15 papers, and in 2 of them, Archimate language is extended.…”
Section: Publication Demographics Analysismentioning
confidence: 99%
“…As a paper can mention more than one EA category element, the total count of elements in Figure 3 is greater than the number of selected publications. Figure 3 reveals that the most common were framework (28), followed by AD papers (21), and views/viewpoints (20). It is noteworthy that Archimate is mentioned in a total of 15 papers, and in 2 of them, Archimate language is extended.…”
Section: Publication Demographics Analysismentioning
confidence: 99%
“…Authors [4,9,10,28] found that BR specifically prepared for the project positively affect software implementation project success because they can help in specifying requirements, software design, software architecture and creating test cases.…”
Section: Rq2mentioning
confidence: 99%
“…Authors [4,9,10,28] found that easy-to-understand BR positively affects software implementation project success since such BR are typically easier to reuse, have a lighter impact on business model complexity, and are easier to modify [30]. According to L'Erario et al [22], business rules are often the core of software development, thus the developer's understanding of business rules and the customer's ability to relate to them is the starting point of a successful software project.…”
Section: Rq4mentioning
confidence: 99%
“…In different contexts from those investigated by our approach, studies have also been conducted to explore the use of BDD as part of empirical analysis of acceptance test-driven development [26]. Other studies have concentrated in the use of automated acceptance testing to support BDD traceability [21], or in analyzing its compatibility with business modeling [8], [9], enterprise modeling [47], [48], [46] and with BPMN [23].…”
Section: Related Workmentioning
confidence: 99%